2004
DOI: 10.1590/s0100-879x2004001200005
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in IFN-gamma-activated murine macrophages

Abstract: Macrophages are critical for natural immunity and play a central role in specific acquired immunity. The IFN-γ activation of macrophages derived from A/J or BALB/c mice yielded two different patterns of antiviral state in murine hepatitis virus 3 infection, which were related to a down-regulation of the main virus receptor. Using cDNA hybridization to evaluate mRNA accumulation in the cells, we were able to identify several genes that are differently up-or down-regulated by IFN-γ in A/J (267 and 266 genes, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Only resistant A/J macrophages show a decreased expression of the gene encoding for the principal viral receptor (Bgp 1a ) [3]. Our quantitative biology studies [1, 4] showing upregulated and downregulated proteins and genes in resistant and susceptible macrophages opened a great perspective for investigations of the biological role of these cells and have also confirmed the downregulation of an MHV3 receptor gene by IFN‐γ activation [4].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Only resistant A/J macrophages show a decreased expression of the gene encoding for the principal viral receptor (Bgp 1a ) [3]. Our quantitative biology studies [1, 4] showing upregulated and downregulated proteins and genes in resistant and susceptible macrophages opened a great perspective for investigations of the biological role of these cells and have also confirmed the downregulation of an MHV3 receptor gene by IFN‐γ activation [4].…”
Section: Introductionmentioning
confidence: 75%
“…These proteomic studies – done years before the term ‘proteomics’ was invented – represented a turning point in my approach to understanding the basis of anti‐MHV state induced by IFN‐γ. A few years later, supported by the Swiss National Science Foundation, we have found that IFN‐γ was capable of inducing a downregulation of the main viral receptor only in macrophages originated from resistant mice, explaining at least in part the cellular and molecular basis of mouse resistance to MHV infection [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, INF-g has been found to downregulate expression of ACE2 (the receptor for SARS-CoV-2), 5 and this downregulation in macrophages is correlated with the latter becoming refractory to infection with the closely related coronavirus MHV3. 6 Collectively, these noteworthy studies suggest that perhaps we may have largely focused on the wrong arm of the immune response. These insights bode well for those vaccines, such as mRNA or DNA vaccines, that express viral proteins from within the context of a cell to induce a cell-mediated response.…”
mentioning
confidence: 99%